IBM z/OS V2R2 operations - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2015)
This IBM Redbooks publication helps you to become familiar with the technical changes that were introduced into the Operations areas with IBM z/OS V2R2. Changes include: how to set up job cancel decisions and region and MEMLIMIT values, new REGIONX JCL keyword that supports two storage specifications, ability to have open up to 2,000,000 data sets at a time by address spaces, new SMF record that is used to track dynamic APF changes, new message that is used to identify the initial program load (IPL) device and volume, enhancements to Infoprint, monitor capture diagnostics for problem determination, record changes to hardware, provisioning that is dynamically based on CPU consumption, and new functions and interfaces of System Rexx. --
Number on resource description page: SG24830500. - "Z Systems.". - Includes bibliographical references. - Online resource; title from cover page (Safari, viewed January 22, 2016)
Keywords: z/OS; Information storage and retrieval systems -- Management; Database management; Bases de données; Gestion; Information storage and retrieval systems; Management